GAGASAN ILMU HADIS MOHAMMAD HASHIM KAMALI: SOROTAN TERHADAP A TEXTBOOK OF HADITH STUDIES - Miftachurrozaq, Tahmid; Husna, Jannatul; Waharjani, Waharjani (Jurnal Ilmiah Ilmu Ushuluddin, 2022)
This study is the thought of Mohammad Hashim Kamali in the science of hadith which is contained in the book A Textbook of Hadith Studies. This research aims to provide an overview of the critical methodology and criteria for the science of hadith, as well as to try to verify the accuracy of the text and the authenticity of the hadith. This research uses a qualitative research approach with the type of library research and historical research. The results of the study state that Kamali's thoughts only provide a glimpse of the efforts of the scholars and hadith scholars to verify the authenticity of the Prophet's hadith. The wealth of scientific works on the methodology of hadith science and the efforts made to compile many works on hadith cover the history of Islamic scholarship. The classification of hadith literature is divided into ten titles. The authors of this work apply certain critical principles, examine the value, advantages and disadvantages of the hadiths they collect, discuss the reliability of the narrators, and explain rare traditions, then examine these works by considering them to be reliable as the main criteria of guidance for narrators hadith. The number of overlapping biographies of hadith bearers is a sign of falsification of hadith. The falsification of hadith should be condemned regardless of any subject.